Philippines Conditional Cash Transfer Program : Impact Evaluation 2012 - World Bank (Washington, DC, 2013)
The specific objectives of the program are to: a) keep children in school, b) keep children healthy, and c) invest in the future of children. It reflects the Government's commitment to promoting inclusive growth by investing in human capital to improve education and health outcomes for poor children and pregnant women. The program is based on the premise that poverty is not about income alone but is multi-dimensional, and factors such as access to basic social services and social environments matter. This report presents the findings from an analysis that assessed program impact by comparing outcomes in areas that received Pantawid Pamilya with outcomes in areas that did not receive the program. The impact evaluation applied two analytical methods: 1) Randomized Control Trial (RCT), which compared randomly assigned program areas and non-program areas to assess program impact, and 2) regression discontinuity design, which compared the outcomes of poor households who received the program with similar poor households just above the poverty line. This report presents the findings from the RCT component only. It should be noted that although 2.5 years of program implementation is generally considered enough time to observe impacts on short-term outcomes, it is not long enough to assess impacts on long-term outcome measures. The program is also achieving its objective of enabling poor households to increase their investments in meeting the health and education needs of their children. Although the study found that the cash grants were reaching beneficiaries, the study did not find an overall increase in per capita consumption among the poor benefiting from the program, although there was some evidence that poor households are saving more in certain provinces.